SnO2 / SnS2 / Ag2S nano material for whitening and sterilizing teeth through piezoelectric electro-catalysis
By using SnO2/SnS2/Ag2S ternary semiconductor heterojunction nanomaterials and combined with piezoelectric photocatalytic technology, the existing teeth whitening and sterilization materials have been solved, and efficient teeth whitening and sterilization effects have been achieved, and biosafety has been ensured.
Patent Information
- Application Number
- CN202411824690.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing dental whitening and sterilization nanomaterials have a single type, low electron hole separation efficiency, poor whitening and sterilization effect, low biosafety and great side effects.
SnO2/SnS2/Ag2S ternary semiconductor heterojunction nanomaterial is adopted to improve the ROS generation efficiency under the synergistic effect of photoacoustics through piezoelectric photocatalytic technology, and achieve teeth whitening and sterilization.
It significantly improves the teeth whitening and sterilization effect, is simple to operate, does not require professional equipment, is highly biosafe, does not damage the surface structure of the teeth, and provides long-term effective antibacterial whitening effect.
Smart Images

Figure CN119632857A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the research field of tooth whitening and sterilization, and relates to the preparation and application of SnO2 / SnS2 / Ag2S nanomaterial with piezoelectric photocatalytic tooth whitening and sterilization performance. Background Art
[0002] With the progress of society, people's demand for oral health care is increasing, and having healthy and white teeth has become an important part of oral care. Cariogenic bacteria represented by Streptococcus mutans adhere to the surface and gaps of teeth to form yellow dental plaque, which is difficult to completely remove by ordinary brushing and flossing. It is the culprit for the discoloration of teeth and the occurrence and development of various oral diseases such as caries. In addition, there are many smokers in my country, and there are at least 800 million people in China who need teeth whitening, plus people with coffee stains, tea stains, etc. Therefore, the development of safe and effective nanomaterials and preparation methods with both tooth whitening and bactericidal functions has a very broad application prospect.
[0003] Currently, one of the important strategies for tooth whitening and sterilization based on nanomaterials is photodynamic therapy (PDT), which uses light energy to excite photosensitive materials to produce hydroxyl radicals, superoxide radicals and other light-triggered reactive oxygen species (ROS), to achieve the purpose of whitening teeth and killing bacteria. In PDT therapy, due to the fast recombination rate of photogenerated carriers, recombination occurs before they migrate to the surface, the generated ROS is limited, the light conversion efficiency is low, and the tooth whitening and sterilization performance is poor.
[0004] Piezoelectric photocatalysis is essentially a new technology that combines photoacoustic power. In this technology system, the material has both piezoelectric and photocatalytic properties. When the piezoelectric photocatalytic material is simultaneously exposed to the synergistic effects of light and ultrasound, the electrons and holes generated by light energy will be effectively separated under the induction of the polarized electric field, and react with small molecules such as water and oxygen to produce ROS, greatly improving the generation efficiency of ROS.
[0005] Piezoelectric photocatalytic nanomaterials with tooth whitening and sterilization functions must not only have excellent piezoelectric photocatalytic performance, but also have good biosafety. At present, the reported piezoelectric photocatalytic tooth whitening and sterilization nanomaterials mainly include Cu-doped Bi2WO6, g-C3N 4-x / Bi2O 3-y If we want to truly apply piezoelectric photocatalytic technology to tooth whitening and sterilization, we urgently need to develop more new nanomaterials with excellent piezoelectric photocatalytic tooth whitening and sterilization functions and their preparation methods.
[0006] In summary, the development of new piezoelectric photocatalytic tooth whitening and sterilization nanomaterials and their preparation methods plays a vital role in promoting this new oral care technology to long-term oral health care treatment applications. Summary of the invention
[0007] One of the purposes of the present invention is to provide a nano material with piezoelectric photocatalytic tooth whitening and sterilization properties to solve the problem of the single type of existing tooth whitening and sterilization nano materials.
[0008] The second purpose of the present invention is to provide a method for preparing the piezoelectric photocatalytic nanomaterial.
[0009] The third purpose of the present invention is to provide an application of the piezoelectric photocatalytic nanomaterial in tooth whitening and sterilization, so as to solve the problems of low electron-hole separation efficiency, unsatisfactory whitening and sterilization effect, low biosafety and large side effects of existing tooth whitening and sterilization materials.
[0010] To achieve the above objectives, the nanomaterial with piezoelectric photocatalytic teeth whitening and sterilization properties described in the present invention is a SnO2 / SnS2 / Ag2S ternary semiconductor heterojunction nanomaterial formed by SnO2, SnS2 and Ag2S, which has the effect of piezoelectric photocatalytic teeth whitening and sterilization.
[0011] The SnO2 / SnS2 / Ag2S nanomaterial preparation and piezoelectric photocatalytic tooth whitening and sterilization performance research provided by the present invention mainly include the following technical steps:
[0012] 1. Preparation of SnO2 / SnS2 / Ag2S nanomaterials. The specific steps are as follows:
[0013] Step 1: Weigh 0.756 g of anhydrous stannous chloride (SnCl2), 2.94 g of sodium citrate (Na3C6H5O7·2H2O), and 1 g of polyvinyl pyrrolidone (PVP) and dissolve them in 10 mL of water, then add 20 mL of anhydrous ethanol and stir at room temperature for 30 min;
[0014] Step 2: Transfer the above 30 mL reaction solution to a 50 mL reactor, perform hydrothermal reaction at 180°C for 12 h, wash with deionized water and anhydrous ethanol three times each after cooling, and dry at 60°C for 10 h to obtain SnO2 nanomaterials;
[0015] Step 3: Weigh 261.76 mg of the SnO2 nanomaterial prepared above, and disperse it in 30 mL of dilute hydrochloric acid (5 mL of 37% concentrated hydrochloric acid + 190 mL of water) by ultrasonication;
[0016] Step 4: Weigh 260.99 mg of thioacetamide (TAA), keep the molar ratio of TAA to SnO2 at 2:1, place it into the above SnO2 dilute hydrochloric acid solution and stir for 30 minutes to mix it evenly;
[0017] Step 5: Transfer 30 mL of the mixed solution to a 50 mL reactor, perform hydrothermal reaction at 140 °C for 3 h, cool after reaction, wash the reactants by centrifugation with deionized water and anhydrous ethanol for 3 times each, and vacuum dry at 40 °C for 2 h to obtain SnO2 / SnS2;
[0018] Step 6: Weigh 60 mg of the SnO2 / SnS2 powder prepared above, ultrasonically disperse it in 20 mL of deionized water, weigh an appropriate amount of silver nitrate and dissolve it in 10 mL of water, add it dropwise to the SnO2 / SnS2 dispersion, and stir for 30 min;
[0019] Step 7: Transfer 30 mL of SnO2 / SnS2 dispersion to a 50 mL reactor, perform hydrothermal reaction at 180°C for 2 h, cool after reaction, wash with deionized water and anhydrous ethanol for no less than 3 times, and vacuum dry at 60°C for 4 h to obtain SnO2 / SnS2 / Ag2S nanomaterials.
[0020] 2. Study on the piezoelectric photocatalytic tooth whitening performance of SnO2 / SnS2 / Ag2S nanomaterials
[0021] SnO2 / SnS2 / Ag2S nanomaterials were used for piezoelectric photocatalytic degradation of indigo solution to simulate the degradation of deposited pigments on teeth and explore their teeth whitening ability.
[0022] Step 1: Weigh 5 mg SnO2 / SnS2 / Ag2S, add 5 mL indigo solution (concentration 10 mg / L), and dark-treat for 30 min;
[0023] Step 2: Treat the indigo solution with ultrasound and light for different time periods, centrifuge at 10000 rpm for 10 min to filter out the sample, measure the UV-Vis curve of the remaining solution, and calculate the degradation efficiency of the indigo solution according to the Lambert-Beer law;
[0024] The teeth soaked in black tea were treated with SnO2 / SnS2 / Ag2S nanomaterials piezoelectric photocatalysis to explore the teeth whitening ability.
[0025] Step 1: Take out the teeth soaked in black tea solution for one week, rinse them, and place them in a suspension of SnO2 / SnS2 / Ag2S powder with a concentration of 1 mg / mL for light and ultrasound synergistic treatment. Take photos of the teeth every 2 hours and compare the color scale with the standard tooth color chart to observe the tooth whitening effect.
[0026] 3. Study on the piezoelectric photocatalytic antibacterial properties of SnO2 / SnS2 / Ag2S nanomaterials
[0027] Step 1: Dissolve 3.8 g of broth in 100 mL of deionized water and sterilize in a high pressure steam sterilizer at 121°C for 20 min.
[0028] Step 2: Inoculate 3 mL of mutans Streptococcus (S. mutans) into the sterilized broth nutrient solution and culture the bacteria in a shaker for 24 h (37°C, 100 rpm);
[0029] Step 3: Take 40 μL of bacterial solution, 2 mL of sterilized fresh broth and 50 mg of sucrose and add them to a culture dish with a diameter of 35 mm. Place it in a shaker (37°C, 100 rpm) under anaerobic conditions and culture it overnight for 24 hours to generate bacterial biofilm;
[0030] Step 4: Take 8 mg of SnO2 / SnS2 / Ag2S nanomaterials, add 2 mL of PBS buffer solution, and mix evenly by ultrasonication;
[0031] Step 5: Pour out the broth in the culture dish, wash the biofilm twice with PBS solution to remove free bacteria, pour the above SnO2 / SnS2 / Ag2S nanomaterial dispersion into the culture dish, and seal it with a sealing film;
[0032] Step 6: Treat the culture dish with ultrasound and light for 10 minutes, then increase the ultrasound power for 3 minutes to destroy the biofilm and release the remaining bacteria in the biofilm;
[0033] Step 7: Take 10 μL of liquid from the treated culture dish, put it into a 2 mL centrifuge tube containing 990 μL of PBS solution, and drop 20 μL on the solid agar medium;
[0034] Step 8: Place the coated agar plate into an anaerobic bag and place it in a shaker (37°C, 100 rpm) for overnight culture for 24 hours under anaerobic conditions;
[0035] Step nine: Observe the bacterial culture conditions and use colony counting to analyze the bactericidal ability of SnO2 / SnS2 / Ag2S nanomaterials.
[0036] 4. Study on the degree of damage to the enamel surface of SnO2 / SnS2 / Ag2S nanomaterials
[0037] Step 1: Slice a healthy tooth and soak it in 3% hydrogen peroxide solution for 10 hours and treat it with 1 mg / mL SnO2 / SnS2 / Ag2S dispersed hydraulic electro-photocatalysis for 10 hours.
[0038] After the second step, the surface morphology of the tooth slices treated by the two different methods was observed and compared with the surface structure of the untreated teeth.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] The present invention reports a new preparation method of SnO2 / SnS2 / Ag2S nanomaterials, reports the piezoelectric photocatalytic effect of SnO2 / SnS2 / Ag2S nanomaterials for the first time, and uses them for piezoelectric photocatalytic tooth whitening and sterilization. The operation method is simple, does not require additional professional equipment and professional operators, has obvious whitening and sterilization effects, and does not damage the surface structure of teeth, allowing people to easily obtain long-term and effective antibacterial and whitening effects in daily care. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the XRD of SnO2 / SnS2 / Ag2S nanomaterials.
[0042] Figure 2 TEM and EDS images of SnO2 / SnS2 / Ag2S nanomaterials.
[0043] Figure 3 This is the DRS spectrum of SnO2 / SnS2 / Ag2S.
[0044] Figure 4 This is a diagram showing the degradation effect of SnO2 / SnS2 / Ag2S nanomaterials on food indigo solution.
[0045] Figure 5 The changes in teeth after black tea soaking treated with SnO2 / SnS2 / Ag2S nanomaterial piezoelectric photocatalytic treatment.
[0046] Figure 6 This is a diagram showing the inhibitory effect of SnO2 / SnS2 / Ag2S piezoelectric photocatalytic material on Streptococcus mutans.
[0047] Figure 7 This is the surface structure of tooth enamel after different treatments. DETAILED DESCRIPTION
[0048] Example 1
[0049] 1. Preparation of SnO2 / SnS2 / Ag2S nanomaterials. The specific steps are as follows:
[0050] Step 1: Weigh 0.756 g of anhydrous stannous chloride (SnCl2), 2.94 g of sodium citrate (Na3C6H5O7·2H2O), and 1 g of polyvinyl pyrrolidone (PVP) and dissolve them in 10 mL of water, then add 20 mL of anhydrous ethanol and stir at room temperature for 30 min;
[0051] Step 2: Transfer the above 30 mL reaction solution to a 50 mL reactor, perform hydrothermal reaction at 180°C for 12 h, wash with deionized water and anhydrous ethanol three times each after cooling, and dry at 60°C for 10 h to obtain SnO2 nanomaterials;
[0052] Step 3: Weigh 261.76 mg of the SnO2 nanomaterial prepared above, and disperse it in 30 mL of dilute hydrochloric acid (5 mL of 37% concentrated hydrochloric acid + 190 mL of water) by ultrasonication;
[0053] Step 4: Weigh 260.99 mg of thioacetamide (TAA), keep the molar ratio of TAA to SnO2 at 2:1, place it into the above SnO2 dilute hydrochloric acid solution and stir for 30 minutes to mix it evenly;
[0054] Step 5: Transfer 30 mL of the mixed solution to a 50 mL reactor, perform hydrothermal reaction at 140 °C for 3 h, cool after reaction, wash the reactants by centrifugation with deionized water and anhydrous ethanol for 3 times each, and vacuum dry at 40 °C for 2 h to obtain SnO2 / SnS2;
[0055] Step 6: Weigh 60 mg of the SnO2 / SnS2 powder prepared above, ultrasonically disperse it in 20 mL of deionized water, weigh 3 mg of silver nitrate and dissolve it in 10 mL of water (keeping the mass ratio of SnO2 / SnS2 powder to silver nitrate at 20:1), add it dropwise to the SnO2 / SnS2 dispersion, and stir for 30 min;
[0056] Step 7: Transfer 30 mL of SnO2 / SnS2 dispersion to a 50 mL reactor, perform hydrothermal reaction at 180°C for 2 h, cool after reaction, wash with deionized water and anhydrous ethanol for no less than 3 times, and vacuum dry at 60°C for 4 h to obtain SnO2 / SnS2 / Ag2S nanomaterials.
[0057] The phase of the prepared samples was analyzed by XRD. Figure 1 The figure shows the XRD pattern of the SnO2 / SnS2 / Ag2S sample prepared with a mass ratio of SnO2 / SnS2 to AgNO3 of 20:1, where the asterisk represents the diffraction peak of SnO2, the triangle represents the diffraction peak of SnS2, and the square represents the diffraction peak of Ag2S. Compared with the PDF standard card, it can be seen that the three phases of tetragonal SnO2 (JCPDF41-1445), hexagonal SnS2 (JCPDF23-0677), and monoclinic Ag2S (JCPDF14-0072) are simultaneously visible in the material, proving the formation of SnO2 / SnS2 / Ag2S.
[0058] In order to further understand the structure and composition of the prepared SnO2 / SnS2 / Ag2S samples, we measured the TEM and EDS ( Figure 2 ). As can be seen from the figure, SnO2 / SnS2 / Ag2S is a structure in which nanoparticles are loaded on nanosheets with a size of about 100 nm, and the Sn, O, S, and Ag elements are evenly distributed together, indicating the formation of a SnO2 / SnS2 / Ag2S ternary heterostructure.
[0059] Figure 3 This is the UV-visible absorption spectrum of SnO2 / SnS2 / Ag2S. It can be seen from the figure that the formed SnO2 / SnS2 / Ag2S ternary heterojunction shows strong absorption from the UV to the visible region, where the absorption edge can reach 759nm. Band gap calculation shows that the band gap width of the SnO2 / SnS2 / Ag2S ternary heterojunction is 1.79eV.
[0060] Taking the food pigment indigo as an example, the effect of SnO2 / SnS2 / Ag2S sample on tooth surface adsorption of pigment whitening was simulated. Figure 4 As shown. Figure 4 (a) It can be seen that under the synergistic effect of light and ultrasound, the concentration of indigo solution decreases with time, and the degradation efficiency can reach more than 95% after 45 minutes. Kinetic analysis found that the degradation kinetic curve of SnO2 / SnS2 / Ag2S nanomaterials for edible indigo solution ( Figure 4 c) It conforms to the first-order kinetic reaction, and the reaction rate constant can reach k = 0.06428min -1 .
[0061] Teeth stained with black tea were placed in a 1 mg / mL SnO2 / SnS2 / Ag2S dispersion and treated with piezoelectric photocatalysis for 6 hours. Figure 5 As shown, it has a good teeth whitening effect. After 6 hours of treatment, the tooth color level is improved from C4 to B1.
[0062] like Figure 6 The figure shows the performance test results of the piezoelectric photocatalytic antibacterial film of SnO2 / SnS2 / Ag2S nanomaterials. It can be seen from the figure that after the piezoelectric photocatalytic antibacterial treatment, the antibacterial film of SnO2 / SnS2 / Ag2S has a significant effect, and the antibacterial rate of the biofilm can reach 90% compared with the blank sample.
[0063] Enamel damage experiments show that Figure 7 As shown in the figure, compared with untreated enamel, the surface structure of enamel did not change significantly after SnO2 / SnS2 / Ag2S synergistic treatment for 10 hours, while a large number of pits appeared on the enamel surface after 3% H2O2 treatment for 10 hours. It can be seen that piezoelectric photocatalytic tooth whitening and sterilization has little damage to teeth and high biological safety.
Claims
1. Preparation and application of SnO2 / SnS2 / Ag2S nanomaterials with piezoelectric photocatalytic tooth whitening and sterilization properties.
2. The preparation of SnO2 / SnS2 / Ag2S nanomaterial according to claim 1, characterized in that The process was carried out as follows: Step 1: 60 mg of the prepared SnO2 / SnS2 powder was weighed and ultrasonically dispersed into 20 mL of deionized water; Step 2: Weigh 3 mg of silver nitrate and dissolve it in 10 mL of water, add it dropwise into the SnO2 / SnS2 dispersion, and stir for 30 min; Step 3: Transfer 30 mL of the above dispersion to a 50 mL reactor, perform hydrothermal reaction at 180 °C for 2 h, and then cool; Step 4: Wash the cooled dispersion system with deionized water and anhydrous ethanol for no less than 3 times, and vacuum dry at 60° C. for 4 h to obtain SnO2 / SnS2 / Ag2S nanomaterials.
3. The SnO2 / SnS2 / Ag2S nanomaterial according to claim 1, characterized in that It has piezoelectric photocatalytic properties.
4. The SnO2 / SnS2 / Ag2S nanomaterial according to claim 1, characterized in that Used in the field of teeth whitening and sterilization.
5. The preparation of SnO2 / SnS2 / Ag2S nanomaterial according to claim 2, characterized in that AgNO3 was dropped into the prepared SnO2 / SnS2 dispersion and hydrothermally treated at 180 °C for 2 h.
6. The SnO2 / SnS2 / Ag2S nanomaterial piezoelectric photocatalytic tooth whitening performance test according to claim 4, characterized in that The indigo solution was treated by ultrasound and light synergistically, and the degradation efficiency of the indigo solution was calculated.
7. The SnO2 / SnS2 / Ag2S nanomaterial piezoelectric photocatalytic tooth whitening performance test according to claim 4, characterized in that By treating the teeth soaked in black tea, the whitening effect is reflected by the change in color levels.
8. The SnO2 / SnS2 / Ag2S nanomaterial tooth sterilization performance test according to claim 4, characterized in that Ultrasound and light were used to synergistically treat the biofilm, and colony counting was used to analyze the bactericidal ability of SnO2 / SnS2 / Ag2S nanomaterials.
Citation Information
Cited By
Preparation method and application of magnetic resonance imaging nanoprobe capable of penetrating pancreatic cancer tumor interstitial substance
CN120324645A
Preparation method and application of a magnetic resonance imaging nano probe capable of penetrating pancreatic cancer tumor interstitium
CN120324645B
Tooth bleaching material based on biological heterojunction as well as preparation method and application of tooth bleaching material
CN121287549A
Composite material for treating periodontitis based on photodynamics as well as preparation method and application of composite material
CN121570590A
Antibacterial photodynamic material for treating periodontitis by regulating ROS (reactive oxygen species) through microenvironment response and preparation method of antibacterial photodynamic material
CN121668311A